2016
DOI: 10.1097/jan.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Centered, Collaborative, and Comprehensive Care

Abstract: Recovery from substance abuse and mental health disorders represents a journey through which individuals move beyond treatment of provider-identified problems toward a path of achieving wellness and productive lives. Overcoming obstacles and barriers encountered along the recovery process, individuals reveal their own strengths and resilience necessary to cope, survive, and thrive in the face of adversity. Recovery-oriented system of care (ROSC) is a framework designed to address the multidimensional nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…These frameworks emphasize respect for client diversity, an empowerment of people using substances and provider understanding of the varied impact that trauma and ethnicity/culture have on treatment expectations and experiences [4, 5, 20]. In addition, there are emerging interests in the design of patient-centered approaches for substance use disorder treatment (see for example [2125]). Patient-centered care (PCC) has been widely recommended to strengthen the quality of health care [4, 26, 27] as it can be universally applied across treatments, settings and providers.…”
Section: Introductionmentioning
confidence: 99%
“…These frameworks emphasize respect for client diversity, an empowerment of people using substances and provider understanding of the varied impact that trauma and ethnicity/culture have on treatment expectations and experiences [4, 5, 20]. In addition, there are emerging interests in the design of patient-centered approaches for substance use disorder treatment (see for example [2125]). Patient-centered care (PCC) has been widely recommended to strengthen the quality of health care [4, 26, 27] as it can be universally applied across treatments, settings and providers.…”
Section: Introductionmentioning
confidence: 99%
“…Our study supports previous findings indicating that the lack of standardised processes and evidence-based guidelines widens the gap between theory and practice among PHC units. [ 7 ] Therefore, there is a negative impact on continuity, coordination, comprehensiveness and quality of PHC services for all patient categories [ 15 , 17 ]. A systematic review by Van der Klauw and colleagues (2014) suggested that effective IT systems constitute a core element for operational integration within PHC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the country’s rapidly aging population, along with the high incidence of mental health disorders [ 14 ] and the growing burden of chronic diseases, [ 15 ] necessitate immediate actions towards an integrated, multidisciplinary network of well-coordinated and cost-effective services. Lack of integration can result in fragmentation of care and poor health outcomes, [ 16 ] as well as in problems related to funding, planning, effectiveness and operation of the healthcare system[ 17 ]. Substantial healthcare budget cuts and prolonged delay of major reform are jeopardising the NHS, putting it at risk of becoming unsustainable and ultimately, obsolete [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of recovery-oriented system in mental healthcare in Cyprus may also explain the way the participants perceived themselves during the illness [ 119 ]. The descriptions they chose to portray themselves were mainly negative ones, for example “bad person” or “tormented person”.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported herein with regard to the way participants experience their living with the illness and subsequent therapy, call for the reorganization of the culture of mental healthcare policy in Cyprus towards a more recovery-oriented approach in both community and hospital organizations. Empowerment of the resilience of people living with SMI, participation in decision-making and planning for their own care, along with effective management of pharmacotherapy, need to be the ultimate focus of mental health services [ 119 , 123 ]. Unfortunately, within the mental healthcare system of Cyprus there still exists disease – centered approaches, characterized by limited involvement of mental health services consumers in the design of the therapeutic plan [ 61 ].…”
Section: Discussionmentioning
confidence: 99%